MORTALITY IN PATIENTS WITH RESPIRATORY AND NON-RESPIRATORY CARBAPENEM RESISTANT-MULTIDRUG RESISTANT ACINETOBACTER INFECTIONS - Nasir, Nosheen; Mahmood, Syed Faisal (Journal of Ayub Medical College Abbottabad, 2017)
Background: Mortality from carbapenem-multi-drug resistant Acinetobacter infections may vary according to site of infection. The objective of this study was to compare mortality in respiratory vs. non-respiratory infection with Carbapenem-Multi-drug Resistant Acinetobacter (C-MRAB). Methods: We conducted a prospective cohort study to compare mortality rate in patients with respiratory vs. non-respiratory infection (n=30 each). Results: Results showed that mortality was 40% in the respiratory group compared to 23% in non-respiratory group; the difference was not statistically significant (p=0.165, RR=1.71, CI=0.73-3.75). There was a significantly higher prior admission rate in patients with respiratory infection (p=0.028). Logistic regression did not reveal any modifier effect from other variables. Conclusion: This study showed no significant difference in mortality in patients with carbapenem-multi-drug resistant acinetobacter respiratory vs. non-respiratory infections. Keywords: Acinetobacter; Mortality; Respiratory; Acinetobacter baumannii; Pneumonia